Effective enhancement of the mechanical properties of macroscopic single-walled carbon nanotube fibers by pressure treatment. Issue 99 (11th October 2016) - Hou, Gu; Wang, Gang; Deng, Ya; Zhang, Jian; Nshimiyimana, Jean Pierre; Chi, Xiannian; Hu, Xiao; Chu, Weiguo; Dong, Hongwei; Zhang, Zhong; Liu, Luqi; Sun, Lianfeng
Abstract : A SWNTs cylindrical fiber is fabricated with diamond wire drawing dies and the SWNT ribbon-like fiber is obtained by pressure treatment. The tensile strength and Young's modulus of ribbon-like fibers can be enhanced with a maximum factor about 55. Abstract : Although individual single-walled carbon nanotubes (SWNTs) show excellent mechanical properties, the tensile strength of macroscopic SWNT fiber is much lower due to the weak junctions and easy sliding among individual SWNTs. In this work, the enhancement of the tensile strength of macroscopic SWNT fibers by pressure treatment is reported. The SWNT films grown by chemical vapor deposition are made into a macroscopic cylindrical fiber with diamond wire drawing dies. The SWNT cylindrical fibers are treated into ribbon-like fibers with a laboratory press in the pressure range of 1.0–4.0 GPa. The tensile strength, Young's modulus, breaking elongation and apparent density of ribbon-like fibers are measured. The experimental results show an effective enhancement in tensile strength of the ribbon-like fibers comparing to that of SWNT cylindrical fibers, suggesting great potentials in improving the mechanical properties of SWNT fibers due to the simplicity and feasibility of pressure treatment.